P211 Vaccination against Sars-Cov-2 in IBD patients: experience from a single tertiary referral centre. (21st January 2022) - Bezzio, C; Guarino, A D; Arena, I; Della Corte, C; Devani, M; Manes, G; Schettino, M; Sablich, E; Vernero, M; Saibeni, S
Abstract: Background: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 have afflicted millions of people in a global pandemic. Recently developed vaccines against SARS-CoV-2 represent one of the most important tool in limiting widespread of infection. However, it is known that vaccination rates in IBD patients are suboptimal. The aim of this study was to compare clinical and socio-demographic features of IBD patients undergoing or not vaccination against SARS-CoV-2, and assess the reasons of who expressed their consent. Methods: A questionnaire was administered to all consecutive IBD contacted by a tertiary referral center for vaccine against SARS-CoV-2 from April 10 th 2021 to May 16 th 2021. Comparisons of prevalence were assessed by Fisher's exact test (significance level p<0.05) Results: 475 IBD patients were contacted by phone call: 28 of them were not reachable, 98 were already vaccinated. Of the remaining 349 IBD patients, 324 (92.8%) accepted to be vaccinated while 25 (7.2%) refused. The questionnaire was compiled by 248/324 (76.5) of accepting and by 19/25 (76.0%) of refusing patients. Their demographic, social and clinical features are shown in Table 1. Among the different variables, only a previous unwillingness to be vaccinated against influenza was associated with the refuse of vaccine anti-SARS-CoV-2. Age, sex, diagnosis, marital status, educational level, employment, previous COVID-19 and biologics and/or immunosuppressants were not associated with the decision to be vaccinated or not. 171 (68.9%) IBD patients have been always pro-vaccine, while the others 77 decided after discussion with their own gastroenterologist (41, 53.2%), relatives (16, 20.8%), general practitioner (9, 11.7%) or according to mass-media (9, 11.7%). The reasons leading to be vaccinated were: duty of collective (190, 76.6%), back to the normality (91, 36.7%) and fear to get sick (71, 28.6%). The possibility to be vaccinated in their own IBD Centre was considered relevant by 141 (56.8%) IBD patients. After vaccine, 67 (27.0%) reported no concerns; the others reported the following: side effects in the short- and long-term (60, 24.2% and 62, 25.0%, respectively), IBD flare (22 (8.9%), interference with IBD medications (19, 7.7%) and inefficacy (18, 7.3%). Conclusion: The majority of IBD patients accepted to be vaccinated against SARS-CoV-2. IBD patients who previously refused vaccine against influenza also refused vaccine against SARS-CoV-2. The possibility to be vaccinated in their own IBD Centre and, among undecided patients, the gastroenterologist recommendations played a relevant role towards the decision to be vaccinated.